HighTeach: A Web-Based Teacher Evaluation System for a Higher Learning Institution in the Philippines - Judith M. Amboya; Rovie M. Francisco; Rene Jay Hernandez; Justine S. Opeña; Ignasius V. Samson; Cris Norman P. Olipas (African Journal of Advanced Pure and Applied Sciences, 2022)
The study is primarily aimed at describing how to design and develop a teacher evaluation system for a higher learning institution in Nueva Ecija, Philippines. Specifically, it sought to describe the activities undertaken in the software development lifecycle stages, including planning and requirements analysis, design, development, and testing. Maintenance and deployment stages were not covered in this study. Using developmental research, proponents developed the system following the SDLC stages. The results show how the proponents successfully developed the system. Proponents suggested that future studies may be conducted which may focus on the assessment phase covering deployment and maintenance stages, to learn how end-users and information technology (IT) experts view the developed system.